Hot Stuff for One Year (HSOY): a 583 million star proper motion catalogue derived from Gaia DR1 and PPMXL - Altmann, Martin; Röser, Siegfried; Demleitner, Markus; Bastian, Ulrich; Schilbach, Elena (Astronomy and astrophysics, 2017)
Context. Recently, the first installment of data from the ESA Gaia astrometric satellite mission (Gaia DR1) was released, containing positions of more than 1 billion stars with unprecedented precision. This release contains the proper motions and parallaxes, however, for only a subset of 2 million objects. The second release will include those quantities for most objects.Aims. In order to provide a dataset that bridges the time gap between the Gaia DR1 and Gaia DR2 releases and partly remedies the lack of proper motions in the former, Hot Stuff for One Year (HSOY) was created as a hybrid catalogue between Gaia and ground-based astrometry. This catalogue features proper motions (but no parallaxes) for a large percentage of the DR1 objects. While not attempting to compete with future Gaia releases in terms of data quality or number of objects, the aim of HSOY is to provide improved proper motions partly based on Gaia data and to allow studies to be carried out now or as pilot studies for later projects requiring higher precision data.Methods. The HSOY catalogue was compiled using the positions taken from Gaia DR1 combined with the input data from the PPMXL catalogue, employing the same weighted least-squares technique that was used to assemble the PPMXL catalogue itself.Results. This effort resulted in a four-parameter astrometric catalogue containing 583 million stars with Gaia DR1 quality positions and proper motions with precisions from far less than 1 mas/yr to 5 mas/yr, depending on object brightness and location on the sky.